EF Fold (Folding Machine) / Nur Atiqah Azhar … [et al.] - Azhar, Nur Atiqah; Mohd Zan, Nurul Fatihah; Azami, Izyan Syazana; Ahmad, Siti Nazatul Ain; Zawawi, Zaim Syahmi; Azis, Siti Noraziana (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
According to the Department of Statistic Malaysia Official Portal, in 2021 as many as 55.1 % or 6.23 million women are no longer housewives, they prefer to work due to the increasingly worrying economy in Malaysia. Working women, on the other hand, frequently have difficulty performing their responsibilities at home flawlessly because they also have chores at work to do. When you have small children who require constant attention and care, the task becomes more difficult. They must also fulfill obligations at home, such as cleaning and cooking. Those with large families will also definitely have trouble tidying up the house especially folding clothes. Therefore, EF Fold aims for wives or women who work to use our product which is a folding machine that makes it easier for them to fold a lot of clothes in a short time. Easy fold is the only one that has innovated this product with a new version that became a hot trending topic in business after its launch. Easy fold machine can save time for wives, especially those who are busy working because this machine can fold 40 clothes in 8 minutes. Our machines will also be marketed at a reasonable price so that everyone regardless of the upper or lower class afford our machines.